Does Globalization Impact Entrepreneurship? - Darlington Akaiso; Mariya V. Markova (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This paper examines the effect of the globalization phenomenon and its impact on the dynamic development of entrepreneurship based on changing economic, cultural, and business environments both within and between nations. Design/methodology/approach: The authors use theoretical perspectives and analyze literature reviews to identify the effect of the relationship that exists between globalization and entrepreneurship, which plays a variety of important roles in the business world. Findings: The findings of the study show that while there is a significant statistical difference between U.S. and international entrepreneurs regarding the importance of cross-cultural considerations, there are no statistical differences regarding the importance of global entrepreneurial innovation, business environment, and the effect of globalization on the economy. Research limitations/implications: The paper presents a critical analysis of the impact of globalization on entrepreneurs in the U.S. and internationally. Practical implications: The authors investigate the characteristics necessary for entrepreneurs to be successful, such as skills, knowledge, experience, and the abilities needed to apply technology and innovation, and they navigate complex cultural differences that may exist between business members and stakeholders from diverse cultural backgrounds. Paper type: Research paper